PEMBELAJARAN MEANS END ANALYSIS DAN PEMBELAJARAN MISSOURI MATHMATICS PROJECT TERHADAP KEMAMPUAN PEMECAHAN MASALAH DAN KEMAMPUAN BERFIKIR KRITIS - Meutia Silvi; Syarbaini Saleh; Reflina (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2021)
Penelitian ini bertujuan untuk mengetahui Pengaruh Model Pembelajaran Means Ends Analysis (MEA) dan Model Pembelajaran Missouri Mathematic Project (MMP) Terhadap Kemampuan Pemecahan Masalah dan Kemampuan Berpikir Keritis di kelas XI MAS PAB 2 Helvetia T.P 2020/2021. Hasil temuan menunjukkan (1) Terdapat pengaruh model pembelajaran Means Ends Analysis (MEA) dan Missouri Mathematic Project (MMP) terhadap kemampuan pemecahan masalah siswa pada materi turunan fungsi aljabar di kelas XI MAS PAB 2 Helvetia, dengan Fhitung (12,944) > Ftabel (3,30). (2) Terdapat pengaruh model pembelajaran Means Ends Analysis (MEA) dan Missouri Mathematic Project (MMP) terhadap kemampuan Berpikir Keritis siswa pada materi turunan fungsi aljabar di kelas XI MAS PAB 2 Helvetia, dengan Fhitung (11, 383) > Ftabel (3,30 ). (3) Terdapat pengaruh model pembelajaran Means Ends Analysis (MEA) dan Missouri Mathematic Project (MMP) terhadap kemampuan pemecahan masalah dan kemampuan berpikir keritis siswa pada materi turunan fungsi aljabar di kelas XI MAS PAB 2 Helvetia, dengan Fhitung (46,411) > Ftabel (3,99). Kata Kunci : Means Ends Analysis (MEA); Missouri Mathematic Project (MMP) ;Kemampuan Pemecahan Masalah; Kemampuan Berfikir Kritis ABSTRACT This study aims to determine the effect of the Means Ends Analysis (MEA) learning model and the Missouri Mathematical Project (MMP) learning model on problem-solving abilities and critical thinking skills in class XI MAS PAB 2 Helvetia T.P 2020/2021. The findings show (1) There is an effect of the Means Ends Analysis (MEA) and Missouri Mathematical Project (MMP) learning models on students' problem solving abilities on the derivative material of algebraic functions in class XI MAS PAB 2 Helvetia, with Fcount (12,944) > Ftable (3 ,30). (2) There is an effect of the Means Ends Analysis (MEA) and Missouri Mathematical Project (MMP) learning models on students' Critical Thinking abilities on the derivative material of algebraic functions in class XI MAS PAB 2 Helvetia, with Fcount (11, 383) > Ftable (3, 30). (3) There is an effect of the Means Ends Analysis (MEA) and Missouri Mathematical Project (MMP) learning models on the problem- solving abilities and critical thinking skills of students on algebraic function derivative material in class XI MAS PAB 2 Helvetia, with Fcount (46,411) > Ftable ( 3.99). Keywords: Means Ends Analysis (MEA); Missouri Mathematical Project (MMP); Problem Solving Ability; Critical Thinking Ability